PENGARUH JOB INSECURITY DAN PSYCHOLOGICAL STRAINS TERHADAP JOB PERFORMANCE KARYAWAN GENERASI MILENIAL PERUSAHAAN XYZ DI MASA PANDEMIK COVID-19 - Yohana F. Cahya Palupi Meilani (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2022)
This study aims to determine the effect of job insecurity on the performance of non-manufacturing employees of the millennial generation at XYZ Company and to determine the mediating effect of anxiety and emotional exhaustion, as well as the moderating effect of intrinsic motivation and supervisor support. This was motivated by the condition of the workforce in the manufacturing industry during the COVID-19 pandemic, which experienced many layoffs. Data collection by distributing questionnaires to respondents who are millennial generation employees of XYZ company who have worked for mimimum one year. Sampling is carried out by sensus to all millenial generation employees. Pilot tests were conducted on 30 people tested for validity and reliability. The actual questionnaires were distributed to 79 people, and 60 questionnaires met the criteria for analysis. The data is processed by Partial Least Square using the SmartPLS 4.0 to test the outer model and inner model. The results of the study show that job insecurity can have a negative effect on psychological strain and employee performance of the millennial generation of XYZ Company. Then, psychological strain can have a negative effect on the performance of millennial employees. The contribution of this research provides input to the management of manufacturing companies, especially XYZ to understand how to improve the performance of millennial generation employees through understanding job insecurity and the role of psychological strain (anxiety and emotional exhaustion)BAHASA INDONESIA ABSTRACTPenelitian ini bertujuan mengetahui pengaruh job insecurity terhadap kinerja karyawan non pabrikasi usia generasi milenial di Perusahaan XYZ serta mengetahui pengaruh mediasi dari anxiety dan emotional exhaustion, serta pengaruh moderasi dari intrinsic motivation dan supervisor support. Hal ini di latarbelakangi oleh kondisi tenaga kerja di industri pabrikasi saat pandemik covid-19 banyak mengalami pemutusan hubungan kerja. Pengumpulan data dilakukan dengan cara menyebarkan kuesioner kepada responden yang merupakan karyawan generasi milenial perusahaan XYZ yang sudah bekerja minimal dua tahun. Kuesiner disebarkan dengan cara sensus terhadap seluruh karyawan generasi milenial yang sudah bekerja minimal 1 tahun di Perusahaan XYZ. Pilot tes dilakukan terhadap 30 orang yang kemudian diuji validitas dan reliabilitas. Setelah itu baru dilakukan penyebaran kuesioner aktual kepada 68 orang, diperoleh 60 kuesioner yang memenuhi kriteria untuk analisis. Data diolah dengan Partial Least Square menggunakan program SmartPLS 4.0 untuk dilakukan uji outer model dan inner model. Hasil penelitian menunjukkan job insecurity dapat berpengaruh negatif terhadap psychological strain dan kinerja karyawan generasi milenial Perusahaan XYZ. Kemudian, psychological strain dapat berpengaruh negatif seperti terhadap kinerja karyawan generasi milenial. Kontribusi penelitian ini memberikan input pada pengelola perusahaan pabrikasi khususnya XYZ untuk memahami bagaimana meningkatkan kinerja karyawan generasi milenial melalui pemahaman job insecurity dan peran psychological strain .